Evaluation of financing of digital economy projects in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2019)
The aim of the study is to assess the financing of digital economy projects, which is a priorityfor the Republic of Kazakhstan in modern conditions. State programs of informatization and digitalizationare carried out over the past years, since the development of information and digital technologieshas a significant impact on the competitiveness of the country. Digital space covers the countries of nearand far abroad, including neighboring countries that interact with Kazakhstan, as a result of which mutualeconomies are enriched. The CIS countries united in the Eurasian Economic Union (EAEU) have not onlycommon borders, but also economic, scientific and technical interests, including on the ground, undergroundand in space. All of the above determines the relevance of the research topic, which considers thepossibilities and the need for funding pilot projects related to digitalization. The scientific significance ofthe study is based on the study of the theory and practice of project activities, especially in the field ofthe digital economy. The practical significance of the study is justified by the possibility of using researchmaterials in the expert evaluation of projects submitted for financing by international, state and corporatefunds. The research was carried out within the framework of accessible information of international, stateand public organizations, as well as scientific and practical publications of those leading in the periodicalpress and the Internet. The study was conducted using analytical, comparative and evaluation methods,based on statistical data, on which relevant conclusions were drawn and recommendations were made.